Correlation Between TNF-α Levels and APRI Score with Ejection in Hepatic Cirrhosis - Muslim Thaher; Triyanta Yuli Pramana; Heru Sulastomo; Dhani Redhono; Eti Poncorini Pamungkasari (Gema Lingkungan Kesehatan, 2026)
Cirrhotic cardiomyopathy is a condition of heart dysfunction characterized by impaired myocardial contractility, left ventricular hypertrophy, diastolic dysfunction, chronotropic dysfunction, and electrophysiological disturbances of the heart. One of the complications in patients with hepatic cirrhosis is influenced by several factors, particularly TNF-α levels and the APRI score. This study aimed to analyze the effect of TNF-α and APRI score on ejection fraction in Child-Pugh C hepatic cirrhosis. Methods: This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 40 inpatients with Child-Pugh C hepatic cirrhosis at the dr. Moewardi Surakarta Regional General Hospital. Samples were selected using consecutive sampling. Data analysis was performed using Spearman’s correlation test and linear regression. Results: The correlation between TNF-α levels and ejection fraction in Child-Pugh C hepatic cirrhosis is r = -0.559, p<0.001 (moderate correlation). The correlation between APRI score and ejection fraction in Child-Pugh C hepatic cirrhosis is r = -0.445, p<0.001 (moderate correlation). There is a significant correlation between TNF-α levels and APRI score with ejection fraction in Child-Pugh C hepatic cirrhosis. The implication is that clinicians may incorporate TNF-α levels and the APRI score into clinical algorithms to monitor cirrhotic patients who are at high risk of developing cardiovascular complications.